Encephalitis and cytokine storm secondary to respiratory viruses in children: Two case reports - Santos, Pollyana C. P.; Holloway, Adrian J.; Custer, Jason W.; Alves, Tomaz; Simon, Liliana (Frontiers in Pediatrics, 2023)
Introduction: Encephalitis is a syndrome characterized by brain damage secondary to an inflammatory process that is manifested by cognitive impairment and altered cerebral spinal fluid analysis; it may evolve with seizures and coma. Despite viral infections representing the main cause of encephalitis in children, respiratory syncytial virus and parainfluenza virus are mostly associated with respiratory presentations. Uncommonly, the inflammatory phenomena from encephalitis secondary to viral agents may present with an exacerbated host response so-called cytokine storm. The link between these infectious agents and neurologic syndromes resulting in cytokine storm is rare and the underlying pathophysiology is still poorly understood. Case presentation: a 5-year-old female and a 2-year-old male infected with parainfluenza and respiratory syncytial virus, respectively, were both identified through nasopharyngeal PCR. They were admitted into the pediatric intensive care unit due to encephalitis and multiple organ dysfunction manifested with seizures and hemodynamic instability. MRI findings from the first patient revealed a bilateral hyper signal on FLAIR in the cerebral hemispheres, especially in the posterior parietal and occipital regions. She also had elevated IL-6 levels during the acute phase and evolved with a fast recovery of the clinical presentations. The second patient progressed with general systemic complications followed by cerebral edema and death. Conclusion: Encephalitis secondary to respiratory viral infection might evolve with cytokine storm and multiorgan inflammatory response in children.